Normothermic ex vivo heart perfusion with NLRP3 inflammasome inhibitor Mcc950 treatment improves cardiac function of circulatory death hearts after transplantation - Xu, Liwei; Zeng, Zifeng; Niu, Chuanjie; Liu, Deshen; Lin, Shaoyan; Liu, Xiu; Szabó, Gábor; Lu, Jun; Zheng, Shaoyi; Zhou, Pengyu (Frontiers in Cardiovascular Medicine, 2023)
Background: The utilization of donation after circulatory death (DCD) hearts can enlarge the donor pool. However, DCD hearts suffer from serious ischemia/reperfusion injury (IRI). Recent studies found that the activation of NLRP3 inflammasome could play a significant role in organ IRI. Mcc950, which is a novel inhibitor of the NLRP3 inflammasome, can be applied to treat various kinds of cardiovascular diseases. Therefore, we hypothesized that the treatment of mcc950 could protect DCD hearts preserved with normothermic ex vivo heart perfusion (EVHP) against myocardial IRI via inhibiting NLRP3 inflammasome in a rat heart transplantation model of DCD. Methods: Donor-heart rats were randomly divided into four groups: Control group; Vehicle group; MP-mcc950 group; and MP+PO-mcc950 group. Mcc950 was added into the perfusate of normothermic EVHP in the MP-mcc950 and MP+PO-mcc950 groups, and was injected into the left external jugular vein after heart transplantation in the MP+PO-mcc950 group. Cardiac functional assessment was performed. The level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome-associated protein of donor hearts were evaluated. Results: The treatment with mcc950 significantly increased the developed pressure (DP), dP/dtmax, and dP/dtmin of the left ventricular of DCD hearts at 90 minutes after heart transplantation in both MP-mcc950 and MP+PO-mcc950 groups. Furthermore, mcc950 added into perfusate and injected after transplantation in both MP-mcc950 and MP+PO-mcc950 groups significantly attenuated the level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome compared with the vehicle group. Conclusions: Normothermic EVHP combined with mcc950 treatment can be a promising and novel DCD heart preservation strategy, which can alleviate myocardial IRI via inhibiting NLRP3 inflammasome.